Evidence‐based Review of Gastrointestinal Bleeding in the Chronic Kidney Disease Patient. Issue 1 (12th September 2014) - Kalman, Richard S.; Pedrosa, Marcos C.
Abstract Patients with end‐stage renal disease are more likely to suffer from gastrointestinal (GI) problems, including bleeding from upper and lower sources. Peptic ulcer disease is the most common cause of upper GI bleeding, and although there is some debate in the literature regarding whether the frequency of ulcer disease is higher in patients with kidney disease, it is well established that outcomes are worse in patients with compromised renal function. Angioectasias can be found throughout the GI tract and are another common cause of bleeding; management can be divided into localized endoscopic therapy and systemic hormonal treatment, or surgery for refractory cases. The most frequent causes of lower GI bleeding in this population, in addition to angioectasias, are diverticulosis, hemorrhoids, and ischemic colitis.